(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article explores ways and approaches to regulating the activities of gas transport and gas distribution companies. The regulatory and legal basis for the operation of gas distribution and gas transport organizations has been defined. A review of theoretical approaches to understanding the concept of "gas distribution enterprise" and the basic principles of its operation has been carried out. The regulatory framework and a number of principles that guide the subjects of the gas transport system when gaining access to its use have been defined, among them: the safety and continuity of the gas transport system; Equality on the provision and consumption of all gas market players; Compliance with quality indicators of services provided by the gas transport system operator; timely repayment of debt by the subjects of the gas transport market. In conditions of dynamism of market changes, special attention deserves the normative-legal basis as the main instrument of regulating influence on the activities of the gas transmission system of Ukraine and its regions. The legislative basis regulating the activities of the gas transportation system has recently been fragmented, partly reflecting separate norms that touched strategic importance of Ukrainian economy sectors. In particular, in the laws of Ukraine, and the overwhelming majority of norms and codes were reflected in by-laws of normative legal acts, as well as in some resolutions of the National Commission on Energy Regulation of Ukraine. However, the existing normative legal aspects did not become a prerequisite for the formation of the foundations of integration into European gas space. One of the first fundamental documents in which was carried out an attempt to regulate the gas transportation system and Mutual reconciliation of its subjects became the decrees of the President However, over time, some provisions of legislative documents are outdated and cannot be applied to the dynamics of processes that take place in gas markets. Therefore, in recent years, the regulatory and legal basis for gas transportation has undergone significant reformation.